A multifunctional Eu-based coordination polymer luminescent sensor for highly sensitive and selective detection of Fe3+ and acetone. (1st January 2020) - Yang, Cheng-Bo; Jiang, Chun-Bo; Zhang, Mu-Yin; Chen, Xue; Zou, Ping; Yang, Rui-Wu; Rao, Han-Bing; Wang, Guang-Tu
Graphical abstract: A new Eu-based phosphonate coordination polymer was successfully synthesized by diffusion at room temperature. The obtained coordination polymer can be used as a fluorescent sensor to sensitively and selectively sense Fe 3+ and acetone. Abstract: A new 3D Eu-based coordination polymer, ([Eu(L)(H2 O)3 ]Cl·H2 O)n (1 ) (H2 L = (4-(pyridyl-N-oxide)methylphosphonic acid), was successfully self-assembled via diffusion method at room temperature and characterized by single-crystal X-ray diffraction, elemental analyses, powder X-ray diffraction, thermogravimetric analyses and FT-IR. Single-crystal X-ray diffraction analysis shows that 1 features 3D (4, 5)-connected (3·4·5·6 2 ·7)(3 2 ·4 2 ·5·6 3 ·7 2 ) topological framework with large 1D channels. Photoluminescent spectra of 1 exhibit the strong characteristic luminescence of Eu 3+ . More importantly, sensing experiments exhibit that 1 can be used as a fluorescence sensor for detecting Fe 3+ and acetone with excellent sensitivity, great selectivity, reproducibility and low detection limits for Fe 3+, and acetone are 0.21 μM and 0.0246 vol%. It is the first example of Eu-based phosphonate sensor for simultaneous detection of Fe 3+ and acetone.